Dynamics of the forced wake of a square cylinder with embedded flapping jets. (March 2022) - Chang, Xu; Chen, Wen-Li; Huang, Yewei; Gao, Donglai
Abstract: The dynamics of the wake of a square cylinder forced with active flapping jets located at its rear surface were experimentally investigated at different jet momentum coefficients ( Cu ). The Reynolds number of the experimental study was fixed at 7.30 × 10 3, based on the incoming flow speed and the diameter of the square cylinder. A new free-feedback flapping jet actuator was embedded along the centerline of the square cylinder to generate active flapping jets. A high-speed 2D particle image velocimetry (PIV) system was adopted to measure the dynamic wake flows behind the square cylinder for various test cases. Analytical methods, including proper orthogonal decomposition (POD), dynamic mode decomposition (DMD), and linear stability analysis, were employed to elaborate on the dynamic evolution of the vortical structures behind the square cylinder. In comparison with the natural case without control, the flow structures of the square cylinder wake slightly changed at the lower Cu coefficients of 0.083 and 0.327. The recirculation region was somewhat pushed by the jets discharged from the rear side of the square cylinder. At a higher jet momentum Cu coefficient of 1.772, the effects of the flapping jets on the shear layers were intensified, and the time-averaged turbulent kinetic energy (TKE) and Reynolds shear stress (RSS) distributions were suppressed in the cylinder wake. The DMD was also employed to further study the coherent flow structures in the square cylinder wake, and the intrinsic nature of the effects of the flapping jets was revealed. Both the modal energy and Strouhal number of the main mode were lower than those of the natural case. Finally, the linear stability analysis of the wake flow field indicated that the flapping jets modified the absolute instability region in the wake.